The Soft Chemical Route Improving IT-SOFC Cathode Performance: The Lanthanum Barium Cobaltite Case - Garcés, Diana Andrea (2013)
In this work we studied the oxygen reduction mechanism in three cathodes: cubic La0.5Ba0.5CoO3-δ obtained by Solid State Reaction (SSR) in air at 1100 ºC; a phase with cationic order, laminar structure and tetragonal symmetry, LaBaCo2O6-δ, was obtained by SSR under inert gas at 1150 ºC. An intermediate compound with the same nominal composition was obtained at lower temperature by a soft chemical route involving a sol-gel process. Despite that the crystal structures of the oxides obtained by SSR are different, their microstructures are similar but quite different to that obtained by the soft chemical route. The area specific resistance (ASR) as a function of pO2 was studied at 700 °C by Electrochemical Impedance Spectroscopy (EIS). We found that both, crystal structure and microstructure affect strongly the ASR. Whereas cubic perovskite showed lower ASR than tetragonal, the ASR of the oxide obtained by the chemical route decreased almost one order of magnitude at higher pO2, respect to that obtained by conventional SSR.